The enemy within : how a totalitarian movement is destroying America - Horowitz, David, 1939- (Regnery Publishing, 2021)
The best-selling author argues that the greatest threat facing the United States is the "totalitarian" faction of the Democratic party, such as the leaders of the Women's March and opponents of Brett Kavanuagh's Supreme Court nomination.